Are remittances inducing laziness in households? a reexamination of the evidence - Ducanes, Geoffrey M. (The Philippine Review of Economics, 2012)
This study reexamines the available evidence on the often-repeated claim that international migration of a household member and the resulting remittances typically lead to laziness in the receiving households. The study finds, after replicating previous studies and testing the claim using more recent data, that there is in fact weak or no evidence to support such claim.